Liberal Feminist Perspective on Modern Films: A Conceptual Framework - Dewi Tria Mulinta; M. Bahri Arifin; Setya Ariani (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2026)
The application of liberal feminism to modern film analysis is discussed in this article. Ideas from liberal feminist thinkers such as Mary Wollstonecraft, John Stuart Mill, Rosemarie Tong, and Joyce Trebilcot are incorporated. The researchers used a library research method and conceptual framework approach for this qualitative study to examine how Wollstonecraft's ideas often align with 18th- to 20th-century film themes and how later thinkers broadened liberal feminism concepts to encompass values that relate to modern-themed films. The findings of this research demonstrated that, in line with the theory employed by the researchers, Wollstonecraft's liberal feminism is closely linked to 18th-20th century films, often depicting women's struggles for politics, education, and suffrage, while Mill, Tong, and Trebilcot's liberal feminism aligns with modern films discussing issues like ambition, self-discovery, personal freedom, gender justice, and mono-androgyny. It can be concluded that researchers can explore liberal feminist values like gender justice, autonomy, and equal freedom in analyzing modern films using Mill, Tong, and Trebilcot's ideas.